1993
DOI: 10.1159/000118969
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carbamazepine and Lithium on Affective Disorders

Abstract: Characteristics of the responders and nonresponders to prophylactic treatment with carbamazepine (CBZ) or lithium (Li) were investigated in a retrospective study of 215 bipolar disorder patients who had received more than 2 years of CBZ or Li treatment in Japan. Patients of mania-dominant type, with isolated occurrence of manic and depressive episodes, with onset of the illness below 30 years of age, and with atypical symptomatology, tended to respond favorably to CBZ. Rapid cyclers and patients with a past hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
59
0
5

Year Published

1994
1994
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(65 citation statements)
references
References 7 publications
1
59
0
5
Order By: Relevance
“…In one acute mania study (Post et al 1987) and several prophylaxis studies (Okuma et al 1973;Post et al 1983;Elphick 1985), a high percentage of response was observed in rapid-cycling patients. However, when rapidcycling patients were compared with non-rapid-cycling patients in the recent studies of Okuma (1993), andDenicoff et al (1994, andunpublished observations) in our group, both found a higher prophylactic response rate to carbamazepine in non-rapid cycling patients. Okuma's data are revealing in that the 53% response rate to carbamazepine in those patients with a history of rapid cycling (compared with 76% in those without) is still substantially higher than the 30% response rate observed for lithium in patients with a history of rapid cycling (compared with 64% in those without such a history).…”
Section: Potential Correlates Of Response To the Mood Stabilizersmentioning
confidence: 41%
“…In one acute mania study (Post et al 1987) and several prophylaxis studies (Okuma et al 1973;Post et al 1983;Elphick 1985), a high percentage of response was observed in rapid-cycling patients. However, when rapidcycling patients were compared with non-rapid-cycling patients in the recent studies of Okuma (1993), andDenicoff et al (1994, andunpublished observations) in our group, both found a higher prophylactic response rate to carbamazepine in non-rapid cycling patients. Okuma's data are revealing in that the 53% response rate to carbamazepine in those patients with a history of rapid cycling (compared with 76% in those without) is still substantially higher than the 30% response rate observed for lithium in patients with a history of rapid cycling (compared with 64% in those without such a history).…”
Section: Potential Correlates Of Response To the Mood Stabilizersmentioning
confidence: 41%
“…Retrospective analyses of small studies [61,62] suggested efficacy of CBZ in RC patients. However, the largest retrospective study analysing 215 patients over 2 years gave no evidence of efficacy in RC patients both for CBZ and lithium [63]. This view is supported by a recent double-blind study comparing lithium and CBZ.…”
Section: Valproatementioning
confidence: 99%
“…Com relação ao tratamento profilático, carbamazepina apresentou taxa de resposta de 57% para depressão e 59% para mania. Segundo Okuma (1993) 136 , pacientes com predominância de sintomas maníacos durante o curso da doença, ciclos não circulares, início precoce dos sintomas e sintomas atípicos tendem a apresentar boa resposta farmacológi-ca ao uso da carbamazepina, enquanto história atual ou passada de ciclagem rápida indica má resposta terapêutica com o uso deste fármaco.…”
Section: Tratamentos Da Ciclagem Rápidaunclassified